General and oral health-related quality of life among caregivers of Parkinson's disease patients - Barbosa, Camila Siqueira; Marchini, Adriana M. P. S.; Marchini, Leonardo [UNESP] (Wiley-Blackwell, 2013)
Aim: The aim of the present study was to evaluate the general and oral health-related quality of life among caregivers of patients with Parkinson's disease. Methods: A representative sample (n=80, 19 men and 61 women) of caregivers from SAo Jose dos Campos, Brazil, answered Oral Health Impact Profile (OHIP-14) and Medical Outcomes Study 36-Item Short Form (SF-36) questionnaires, as well as another questionnaire regarding caregivers' characteristics and caring activities. Results: The OHIP-14 average score was 2.56. The SF-36 average score for the domain of physical function was 87.4; for role-physical function, 85.0; for bodily pain, 62.9; for general health, 76.6; for vitality, 80.0; for social function, 88.4; for role-emotional function, 83.8; and for mental health, 85.3. All domains of the SF-36 also showed negative correlations with OHIP-14 in the entire sample, but this correlation could not be observed among lower educated caregivers. There were significant differences between formal and informal caregivers for OHIP-14 and for the majority of SF-36 domains. Conclusions: Most caregivers were female, the mean scores for SF-36 and OHIP-14 were adequate, and formal caregivers had better results for the SF-36 and OHIP-14 when compared with informal caregivers. Geriatr Gerontol Int 2013; 13: 429436.
Keywords: caregivers; Oral Health Impact Profile; Parkinson's disease; Medical Outcomes Study 36-Item Short Form